Paul and the restoration of humanity in light of ancient Jewish traditions - Sherwood, Aaron. (Ancient Judaism and Early Christianity, 2013)
In Paul and The Restoration of Humanity in Light of Ancient Jewish Traditions , Aaron Sherwood questions the assumption of universalism in Pauline thought, and finds instead that relevant Pauline traditions depict a partly restricted and particularly Israelite restoration of humanity. This important Jewish component of Paul's thought remains largely unrecognized, but Pauline and other ancient Jewish traditions consistently present Israel and non-Israelites' uniting in their worship of Yhwh as the restoration of both Israel and humanity. Aaron Sherwood demonstrates in Pauline traditions the same deployment of Israel-nations unification as in biblical and post-biblical traditions. This suggests that rather than secondarily finding space for Gentile justification, the restoration of humanity plays a generative role in Paul's theology, mission, and apostolic self-identity.